Caregivers? perceptions of caregiver burden, quality of life and support needs in caring for a child with cerebral palsy with feeding and/or swallowing difficulties within the context of the Western Cape, South Africa - Le Roux, Raquel (Department of Health and Rehabilitation Sciences, 2024)
Background: Children with cerebral palsy often present with feeding and/or swallowing difficulties and are reliant on family caregivers for long-term care, particularly in resource-constrained countries like South Africa. This can result in caregiver burden and decreased quality of life for both caregiver and child. The planning and implementation of supportive services and interventions depend on the availability of knowledge relating to caregivers' perceptions of burden and the impact on their quality of life, as well as their specific support needs. Research Aim: To describe caregivers' perceptions of caregiver burden, quality of life and support needs in caring for a child with cerebral palsy who has feeding and/or swallowing difficulties, in the context of the Western Cape, South Africa. Methods: A qualitative, descriptive, case study design was utilised to describe the perceptions of eight mothers caring for children with cerebral palsy who have feeding and/or swallowing difficulties, who were between the ages of two and eight years (mean=4.63). Participants, aged between 25 and 42 years (mean = 29.25), were recruited from a hospital's cerebral palsy clinic. Semi-structured telephonic interviews, using an interview guide of seven open-ended questions and probes, were conducted and recorded. Four interviews were conducted in English and the remaining four were conducted in isiXhosa. To ensure trustworthiness and rigor, the study used various measures such as pilot testing, informal member checking, verbatim transcription, re- evaluation of data, triangulation of analysts and sources, debriefing and reflexivity. The data were analysed using thematic analysis to generate themes and sub-themes. Results: Caregiver perceptions were captured in seven key themes, namely: ‘Worry'; ‘Feeding is everything'; ‘Identified support needs'; ‘What helps me cope?'; ‘Cost of caregiving'; ‘Hopeful caregiving'; and ‘Shortfalls of healthcare system and society'. The themes reflect the stress and anxiety of caregiving, the centrality of feeding, specific needs for support, resilience and coping, multifaceted strain, hope and positivity, and failures of healthcare and society in supporting caregivers. Conclusions: The results of this study give voice to caregivers of children with cerebral palsy who have feeding and/or swallowing difficulties, in South Africa. The caregivers highlighted challenges they face in terms of the burden of caregiving and the impact on their quality of life. These caregivers also described the support that was helpful and support that is needed. This knowledge contributes to a broader knowledge base and informs the development of contextually relevant support services for caregivers of children with cerebral palsy who have feeding and/or swallowing difficulties in the Western Cape – and similar contexts – to improve the caregiving experience and quality of life outcomes for caregivers and their children.